(untitled) (AYUSHDHARA, 2023)
Ayurveda is the most ancient among the holistic health science donated to humanity by the perfect Indian heritage. Palitya disease has been explained in all Samhitas in different context. So in Charaka Samhita kala Akala Palitya is mentioned under Sirogata vyadhi, whereas other authors explained it in Sirokapalagata roga and Kshudrarogadhikara. Akala Palitya has been mentioned in the Ayurvedic classics among Sirokapalagata vyadhi, Keshashauklatyam, Kalapurvapakava. Trichological Society defined Premature Canities (Akala Palitya) as a pigment deficiency frequently seen in middle aged people of either gender. Akala Palitya is an accompaniment of premature greying and possesses a clinical challenge to the medical practitioners. In present days because of altered lifestyle and stressful occupation signs of aging are seen much earlier. Increasing urbanization and industrialization has posed greater danger, due to pollution and contamination of water and air, with variable both exogenous and endogenous factors, there is definite increase in the incidence of Premature Greying of Hairs, especially in tropical and developing countries.